Оцінка генетичного поліморфізму чорногірських популяцій Gentiana lutea L. (Gentianaceae) з Українських Карпат: RAPD-аналіз - Мосула, М.З.; Конвалюк, І.І.; Мельник, В.М.; Дробик, Н.М. (Фактори експериментальної еволюції організмів, 2013)
The aim of the work was to study population genetic diversity of three Chornogora populations of Gentiana lutea L. using RAPD markers. Molecular-genetic analysis allows to generate information on species genetic diversity, uniqueness of gene pool in isolated populations and elucidate to what extent they are endangered by the inbred depression. This is essential for further development of scientifically substantiated approaches to conservation of this species. Methods. Genetic variability of 45 plants from three populations of G. lutea was estimated by RAPD-analysis using 10 primers. Results. Comparison of three populations under study revealed similarity of their genetic polymorphism. As evidenced from the dendrogram of the genetic relations between populations, samples from Pozhyzhevska population were closer to Sheshul population one, while those from Lemska mountain valley are genetically more distant. By the results of AMOVA the proportion of distinctions between G. lutea populations within the general distribution of genetic variation made up 72 %, while that of polymorphism inside populations constituted 28 %. Conclusions. Comparison of the data obtained as regards the level of genetic polymorphism in G. lutea with those described for other species from family Gentianaceae found comparable or higher indices of variation in our studies. Our findings may suggest the absence of threat for genetic erosion of this species.